The Ability of Mathematical Reasoning and Self Efficacy Students in Learning Project Based Learning Assisted Moodle - Al Ashari, Shoib Rizal; Mulyono, Mulyono; Mariani, Scolastika (Unnes Journal of Mathematics Education Research, 2021)
This study aims to find out students' mathematical reasoning abilities in Moodle-assisted Project Based Learning in terms of self-efficacy of class XI students at SMA Negeri 5 Semarang. This research is a mixed method type of concurrent embedded design. The subjects of this study were determined based on self-efficacy scores using a self-efficacy questionnaire for class XI students at SMA Negeri 5 Semarang. The results showed that students with high self-efficacy were able to master all indicators of mathematical reasoning: (a) able to analyze problems, (b) able to apply strategies, (c) able to find and use relationships from different mathematical domains, different contexts, and representations. different, (d) interpreting solutions and ways to answer problems, well. Students with moderate self-efficacy category can master three indicators of mathematical reasoning well. Meanwhile, students who have low self-efficacy are only able to master one indicator of mathematical reasoning well